A gel-like/freeze-drying strategy to construct hierarchically porous polyoxometalate-based metal–organic framework catalysts. Issue 11 (22nd February 2018) - Li, Xiao-Hui; Liu, Yi-Wei; Liu, Shu-Mei; Wang, Shuang; Xu, Li; Zhang, Zhong; Luo, Fang; Lu, Ying; Liu, Shu-Xia
Abstract : The synthetic route to hierarchically porous NENU-9 and the enhancement of TOFs in comparison to NENU-9 without hierarchical pores is presented. Abstract : Hierarchically porous metal–organic frameworks combining the merits of micropores with high surface areas and mesopores/macropores with large diffusion channels are highly desired in catalysis, especially for reactions involving large substrates. In this work, a simple and common solvent templating strategy for the construction of hierarchically micro- and mesoporous polyoxometalate-based metal–organic frameworks by a gel-like/freeze-drying method was achieved. Fast nucleation and interconnection of nanoparticles with micropores were realized in the gel-like stage. Subsequently, the synthesized mesopores were strengthened by the squeezing by ice crystals due to volumetric swelling during the process of freezing water into ice. The hierarchically porous material showed improved catalytic activities for the oxidation of alcohols compared to the catalyst without hierarchical pores, due to it having more easily accessible catalytic sites and the acceleration of mass transfer.